Effects of cell salvage on erythrocyte 2, 3‐disphosphoglycerate and G‐6‐PD levels and phosphatidylserine expression. Issue 4 (26th November 2012) - Che, J.; Tian, M.; Ding, G.; Huai, Q.; Dong, P.; Li, Y.; Li, S.
Summary Introduction The aim of this study was to investigate the contribution of the perioperative cell salvage process to the changes in erythrocyte 2, 3‐disphosphoglycerate (2, 3‐DPG) and glucose‐6‐phosphate dehydrogenase (G‐6‐PD) levels and phosphatidylserine (PS) expression using a self‐control study comparing washed blood with venous blood. Methods Thirty patients undergoing elective heart and blood vessel surgery were enrolled. Blood was collected and processed using a Fresenius continuous autotransfusion system device. 2, 3‐DPG and G‐6‐PD activities, as well as PS expression, from both venous and washed red blood cells (RBC) were measured. We also compared these indicators among washed RBC at 6 h, washed RBC at 0 h, and venous RBC. Results 2, 3‐DPG and G‐6‐PD activities in washed blood at 0 h were significantly higher than in venous RBC (2, 3‐DPG, venous vs. washed blood P < 0.05; G‐6‐PD, venous vs. washed blood P < 0.05). Flow cytometry results showed no differences between venous blood and washed RBC at 0 h (n = 23, P > 0.05). 2, 3‐DPG activity in washed RBC that were allowed to stand for 6 h decreased compared with that in venous blood (venous vs. washed blood at 6 h P < 0.01), whereas no significant difference was observed in G‐6‐PD activity (venous. vs. washed blood at 6 h P > 0.05). Conclusion Compared with venous RBC, washed RBC from intraoperative cell salvage exhibited good oxygen‐carrying and antioxidant capacities. However, the oxygen‐carrying capacity of washed RBC that were allowed to stand for 6 h was not as good as that of venous RBC. Thus, we suggest that washed RBC that were left to stand for more than 6 h should not be reinfused.